. TRADITIONAL CHINESE MEDICINE ACUPOINT PASTING FOR PREVENTING AND TREATING GASTROINTESTINAL REACTIONS IN TYPE II DIABETES MELLITUS PATIENTS UNDERGOING GLUCAGON-LIKE PEPTIDE-1 RECEPTOR AGONIST THERAPY: A CLINICAL STUDY: Serum level of glycated Hb (HbA1c), fasting INS (FINS), INS β secretion (HOMA-β), erythrocyte sedimentation rate in Type II Diabetes - Zheng, Jiandi (Journal of Medical Biochemistry, 2025)
Introduction: Serum level of glycated Hb (HbA1c), fasting INS (FINS), INS β secretion (HOMA-β), in Type II Diabetes Mellitus Patients Undergoing Glucagon-Like Peptide-1 Receptor Agonist Therapy were evaluated. Materials and Methods: this study randomly assigned 315 patients starting GLP-1RA therapy into a control group (CG, standard treatment + routine care), a placebo group (PG, placebo + routine care), and a traditional Chinese medicine (TCM) group (TG, TCM plaster therapy + routine care). The glycemic control, pancreatic function, hematological parameters, renal function, and adverse reactions (ARs) were compared among the groups. Results:the TG group exhibited no significant differences in fasting blood glucose (FBG), postprandial blood glucose at two hours, glycated hemoglobin (Hb), fasting insulin (FINS) levels, β-cell insulin secretion, and insulin resistance (IR) when compared to the CG and the PG (P>0.05). Additionally, there were no significant changes in Hb, white blood cell (WBC) count, and erythrocyte sedimentation rate (ESR) in the TG relative to the CG and PG (P>0.05). Renal function indicators revealed that the levels of blood urea nitrogen (BUN) and serum creatinine (Cr) in the TG did not differ significantly from those in the CG and the PG (P>0.05). The incidence of ARs in TG (8.57%) was markedly lower than in PG (17.14%) and CG (18.1%) (P
Keywords: Serum level , glycated Hb (HbA1c), fasting INS (FINS), INS β secretion (HOMA-β), T2DM; GLP-1 receptor agonists; gastrointestinal adverse reactions; glycemic control; insulin